Performance Disparities Of Village Fund Planners And Managers In The Framework Of Accelerating Development (Case Study Of Weri Village, East Fakfak District And Patipi Pasir Village, Teluk Patipi District – Fakfak Regency) - Risyanto Risyanto; Risyana Mirda; Cristina Wulandari; Rifda Fitrianti (Jurnal Scientia, 2024)
The performance of the community together with leaders and officials in the village in preparing development plans and managing village funds is very crucial for accelerating village development and progress. The research aims to uncover the level of disparity in the performance of village planners and village fund managers, which in a structured manner basically starts with the role of all components of the village community itself in order to create accelerated development towards a prosperous village. The research method uses a statistical quantitative analysis approach , the results of which are described using the Ishikawa diagram with a combination of weighting techniques. Research respondents were chosen deliberately, and data mining techniques were carried out by in-depth interviews using questionnaire tools. Data processing uses multi-level qualitative analysis techniques starting with shift share analysis and spider web analysis.